DISEMINASI PENCEGAHAN KEKERASAN, KEKERASAN SEKSUAL, DAN PENYALAHGUNAAN OBAT-OBATAN TERLARANG DI SATUAN PENDIDIKAN - Heri, Ririn Nurfaathirany; Umar, Firman; Tahir, Heri; Gani, Andika Wahyudi; Sari, Dian Novita (Universitas Negeri Makassar, 2024)
Violence among students is increasingly widespread on social media. Cases of bullying, discrimination, brawls, sexual violence and illegal drug abuse are increasingly publicized and seem to be a trend among students. Throughout 2024, the Federation of Indonesian Teachers' Unions (FSGI) recorded various cases of violence in schools, especially bullying and sexual violence. On the other hand, student involvement in drug abuse is also increasing. Students become easy targets because of social and environmental pressure. The Ministry of Women's Empowerment and Child Protection (KemenPPPA) also reported an increase in the prevalence of violence against children. In 2024, physical violence experienced by girls will increase to 15.56%, while emotional violence against boys will reach 43.17%. This type of violence often has a negative impact on the mental and physical health of the victim. Based on this, the UNM PKM Team carried out dissemination on the prevention of violence and illegal drug abuse in educational units.